IMPLEMENTASI KEBIJAKAN TENTANG DESA DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI DESA SASAGARAN KECAMATAN KEBONPEDES KABUPATEN SUKABUMI - Cepta Hery; Wira Saputra Rahman (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The issuance of Law number 6 of 2014 concerning villages is an affirmation which contains an acknowledgment of the position of the village and contains implementing regulations in regulating villages so that they can be used as guidelines and references in implementing village governance and contain consequences that must be followed up. The establishment of the Ministry of Villages and Development of Disadvantaged Regions and Transmigration through Presidential Regulation Number 12 of 2015 is in the context of the task of assisting in carrying out government affairs in the village and rural areas, empowering rural communities, accelerating development of disadvantaged areas and transmigration. Policies issued by the government related to villages are one of the goals for the welfare of all Indonesian people. The village is an area that is in direct contact with community groups who want to be prospered in the context of achieving national goals and functions as an institution that strengthens the structure of the Indonesian state government, therefore, in the implementation of village governance, it must comply with the laws and regulations related to villages which are implemented through village policies.